2015
DOI: 10.1055/s-0035-1565310
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and dereplication strategies in the discovery of natural product derived drugs

Abstract: Metabolomics is the technology designed to provide general qualitative and quantitative profile of metabolites in organisms exposed to different conditions. Metabolomics is applied in many aspects of natural drug discoveries, particularly in bioactivity screening to improve dereplication and identification procedures. Fast dereplication of known compounds and identification of lead bioactive metabolites is important in the primary stages of metabolomics profiling prior to an intensive isolation work. Two level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This meant determination of chemical diversity, which usually occurred after extraction, isolation, and purification had been performed, resulted in high redundancy rates. To overcome this problem, several dereplication methods have been developed. , One example is the use of genetic information on the organism particularly in microorganisms. ,,, However, challenges remain, as it has been shown that even strains with similar 16S gene sequences do not necessarily produce the same chemistry, , indicating that the induction and/or activation of biosynthetic machinery for natural product production is far more complex than originally thought and relies on a complex interaction of environmental, chemical, biochemical, and biological stimuli. , Even if the organism’s metabolome is successfully stimulated, the next challenge is detection and identification of new secondary metabolites that are often produced in small quantities, in a background of known metabolites present in higher quantities. It is therefore imperative to devise new strategies that rapidly identify known compounds early on in the project, so that resources can be concentrated only on the discovery of structurally new or novel ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This meant determination of chemical diversity, which usually occurred after extraction, isolation, and purification had been performed, resulted in high redundancy rates. To overcome this problem, several dereplication methods have been developed. , One example is the use of genetic information on the organism particularly in microorganisms. ,,, However, challenges remain, as it has been shown that even strains with similar 16S gene sequences do not necessarily produce the same chemistry, , indicating that the induction and/or activation of biosynthetic machinery for natural product production is far more complex than originally thought and relies on a complex interaction of environmental, chemical, biochemical, and biological stimuli. , Even if the organism’s metabolome is successfully stimulated, the next challenge is detection and identification of new secondary metabolites that are often produced in small quantities, in a background of known metabolites present in higher quantities. It is therefore imperative to devise new strategies that rapidly identify known compounds early on in the project, so that resources can be concentrated only on the discovery of structurally new or novel ones.…”
mentioning
confidence: 99%
“…13,16 One example is the use of genetic information on the organism 17 particularly in microorganisms. 8,13,18,19 However, challenges remain, as it has been shown that even strains with similar 16S gene sequences do not necessarily produce the same chemistry, 20,21 indicating that the induction and/or activation of biosynthetic machinery for natural product production is far more complex than originally thought and relies on a complex interaction of environmental, chemical, biochemical, and biological stimuli. 8,22 Even if the organism's metabolome is successfully stimulated, the next challenge is detection and identification of new secondary metabolites that are often produced in small quantities, in a background of known metabolites present in higher quantities.…”
mentioning
confidence: 99%
“…Dereplication is now defined as the elimination of known active substances from consideration when a bioactive mixture is being investigated . Since 1978 a diversity of dereplication strategies have been reported. These strategies generally rely upon the ability to match molecular features present in unknown bioactive NPs (either spectroscopic/spectrometric or structural) with data stored in spectroscopic (containing MS and/or 13 C NMR data of NPs) and/or structural databases. A dereplication strategy is generally implemented after initial screening of extracts or semipurified fractions, and the most widely used involve the so-called hyphenated techniques, in which a separation device (a chromatograph) is coupled with spectrometers such as MS, UV, IR, and NMR and analysis of the spectra obtained provides structural information on the compounds present in mixtures. , UV and IR provide the least discriminatory spectroscopic data and can really be used only for dereplication in combination with other spectroscopic data.…”
mentioning
confidence: 99%